Characterizing Intimate Partner Violence-Caused Brain Injury in a Sample of Survivors in the Two Spirit, Lesbian, Gay, Bisexual, Transgender, Queer or Questioning Community - Stranges, Tori N. (Journal of interpersonal violence, 2025)
Research in the field of intimate partner violence-caused brain injury (IPV-BI) has predominantly focused on heterosexual women, ignoring the unique needs of the Two Spirit, Lesbian, Gay, Bisexual, Transgender, Queer or Questioning (2S/LGBTQ) community. The purpose of this exploratory research was to better understand the prevalence of IPV and IPV-BI in 2S/LGBTQ relationships where IPV was defined as physical, psychological, financial, sexual, and/or identity-based abuse from a current of former intimate partner. This study used a cross sectional internet-based survey that ran from September to December of 2022. In addition to descriptive statistics, prevalence rates and their corresponding Wilson Score confidence intervals are reported to estimate the proportion of individuals who experienced IPV and IPV-BI. Finally, for both gender identity and sexual orientation, we tested whether participants with each identity had differing levels of brain injury severity compared to participants who did not hold that identity using Mann–Whitney U tests. In total, 170 2S/LGBTQ+ adults responded to the survey. Among the respondents, 54% identified as Two-Spirit, 24% identified as gay, 17% identified as queer, 14% identified as bisexual, and 8% identified as lesbian or pansexual, respectively. Respondents were predominantly multiracial, post-secondary educated, full-time employed, cisgender women (35%) or cisgender men (19%). The overwhelming majority reported lifetime prevalence of IPV at 98% (n = 166, 95% CI [94.11, 99.08]). Additionally, 68% (n = 115, 95% CI [60.29, 74.22]) of participants reported symptoms consistent with an IPV-BI. These results are consistent with the findings that the 2S/LGBTQ community are at heightened risk of experiencing physical IPV. These findings are the first to our knowledge to report a high rate of symptoms consistent with an IPV-BI in the 2S/LGBTQ population.